The Influence of Jack Billiard Marketing Communication on Increasing the Number of Visitors - Valisya Zilvania; Eraskaita Ginting; Badarudin Azarkasyi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The problem in this study arises from the increasingly fierce competition in the entertainment industry which requires business actors, including Jack Billiard, to be able to implement effective marketing communication strategies to increase the number of visitors. This research focuses on the influence of marketing communication on the increase in the number of visitors and how much Jack Billiard's marketing communication affects the increase in the number of visitors. This study aims to find out and describe the influence of marketing communication and measure how much it contributes to increasing the number of visitors. The research method used is a quantitative approach. The variables of marketing communication were measured using the concept of Integrated Marketing Communication (IMC), while the increase in the number of visitors was measured through the stages of Attention, Interest, Desire, and Action (AIDA). Data were obtained from 97 respondents who were visitors to Jack Billiard through questionnaires, and supported by interviews and documentation. The results of the study show that marketing communication has a significant effect on increasing the number of visitors. This is supported by the effectiveness of promotions through social media, promo offers, employee services, and the delivery of clear and interesting information. Thus, integrated marketing communication is able to increase interest, interest, and the decision of visitors to come and make repeat visits.